Diets high in vegetables, fruits, cereals, and tubers as a protective factor for metabolic syndrome in bank employees - Cattafesta M (Dove Medical Press, 2018)
Monica Cattafesta,1 Luciane Bresciani Salaroli2 1Postgraduate Program in Public Health, Federal University of Espírito Santo, Vitória, Espírito Santo, Brazil; 2Postgraduate Program in Public Health, Postgraduate Program in Nutrition and Health, Department of Health Integrated Education, Federal University of Espírito Santo, Vitória, Espírito Santo, Brazil Background: The prevalence of metabolic syndrome (MetS) is increasing, and its development may be related to westernized diets and working conditions.Purpose: The purpose of this study was to evaluate the association of dietary patterns in bank employees with the presence of MetS, considering sociodemographic and behavioral factors as well as laboratory tests. Subjects and methods: This was a cross-sectional study of 515 bankers. Sociodemographic, occupational, behavioral, and food consumption data were collected. Dietary patterns were determined by principal component analysis with orthogonal varimax rotation.Results: The dietary pattern of vegetables, fruits, cereals, and tubers was correlated with the presence of MetS and with waist circumference measurements and triglyceride levels. Individuals in the third and fifth quintiles of the pattern “vegetables, fruits, cereals, and tubers” presented with 3.28 and 2.24 times less chances of MetS when compared to individuals in the first quintile of this dietary pattern (OR 0.30, 95% CI 0.13–0.67, and OR 0.44, 95% CI 0.21–0.92, respectively). Subjects over 45 years of age were almost twice as likely to develop MetS (OR 1.95, 95% CI 1.01–3.77).Conclusion: Healthy eating represented by the dietary pattern “vegetables, fruits, cereals, and tubers” was associated with better health among bank employees, especially when evaluating competing metabolic complications such as MetS. Keywords: metabolic syndrome, dietary patterns, food consumption, workers, bank employees